The Effect Of Incentive Giving On Employee Performance Through Human Resource Development In Public Works And Spatial Planning Service Asahan Regency - Ilham Bahruddin; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2025)
Proper incentive provision and optimal human resource development are important factors in improving employee performance in government organizations. This study aims to determine and analyze the effect of incentive provision on employee performance mediated by human resource development at the Public Works and Spatial Planning Office of Asahan Regency. This study uses a causal associative quantitative approach. The sample used was the entire employee population of 145 people, with a saturated sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results showed that incentive provision had a positive and significant effect on employee performance, with a T-statistic value of 20.605> 1.96 and a P-value of 0.000 <0.05, indicating that increasing incentives can improve employee performance. In addition, incentive provision had a positive and significant effect on HR development, with a T-statistic value of 55.921> 1.96 and a P-value of 0.000 <0.05, indicating that incentives encourage employee involvement in skill development. Human resource development also has a positive and significant effect on employee performance, with a T-statistic value of 8.826 > 1.96 and a P-value of 0.000 < 0.05, indicating that increasing human resource development can improve employee performance. In addition, human resource development is able to mediate the effect between incentive provision on employee performance, indicated by a T-statistic value of 8.385 > 1.96 and a P-value of 0.000 < 0.05. These results provide insight that incentive provision and human resource development are effective strategies in improving employee performance at the Public Works and Spatial Planning Office of Asahan Regency